Akuntabilitas Laporan Keuangan Dalam Perspektif PSAK 109 (Studi Kasus Pada LAZ DASI NTB) - Baiq Regitha Puji Meilantika; Ida Ayu Nursanty; Rusdi (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This study aims to find out how the financial accountability of zakat institutions is a case study at LAZ DASI NTB. This type of research is descriptive research with qualitative data analysis. To obtain data, researchers use interview, observation and documentation data collection techniques. As a guarantor of data validity, this study uses the validity technique of data triangulation method. All data obtained are then analyzed inductively. The results showed that accountability that can be seen from zakat management at the Amil Zakat DASI NTB Institute consists of four aspects, namely the preparation of financial statements quickly and precisely, the audit committee, monitoring work programs, evaluating work programs. Based on the research focus, namely financial accountability based on PSAK 109, the LAZ DASI NTB shows the results that LAZ DASI NTB is accountable and financial statements are prepared based on PSAK 109.